O papel do Comitê da Bacia Hidrográfica do Paraná 3 na gestão e conservação da água - Sornberger, Neimar Afonso (2015)
This paper aims at discussing about water management in Paraná Basin 3 - BP3, whose focus is on the role of the BP3 Committee, management and conservation of water resources. The interdisciplinary dialogues presented here are guided in the environmental crisis on the perspective of modernity risks and the Science role; the right to an ecologically balanced environment and drinking water and; water management based on the Integrated Management of Water Resources, concerning the nowadays legal framework in Brazil and Paraná State. The overall purpose of this research is to study water resources management within the BP3, from the National Water Resources Policy of 1997 and the BP3 Committee. This is an exploratory study according to its goals, which is also classified as a case study. Data were obtained from questionnaires or semi-structured interviews with members of the BP3 Committee and the representative of the Basin Management BP3 (integrated into the Institute of Paraná waters), in 2014. Its results are analyzed and presented in accordance with the theoretical and methodological assumptions according to Bardin's content analysis (1995) and aim at contributing to further discussions regarding water resources management. In addition, this trial has instigated some reflections recommended by the Post-Graduation Program in Sustainable Rural Development (PPGDRS) at the Western Paraná State University (Unioeste), structured at the Concentration Area of Sustainable Rural Development